Beyond the reactive‐proactive dichotomy: Rage, revenge, reward, and recreational aggression predict early high school bully and bully/victim status. Issue 5 (29th June 2018) - Runions, Kevin C.; Salmivalli, Christina; Shaw, Therese; Burns, Sharyn; Cross, Donna
Abstract : The role of reactive and proactive aggression in school bullying perpetration remains unclear. In this study, we explore the predictive value of an expanded model of aggression motives based on the Quadripartite Violence Typology (QVT), which distinguishes between motivational valence (appetitive or aversive) and recruitment of deliberative self‐control to derive four classes of motives: Rage, Revenge, Reward, and Recreation. With a sample of 1, 802 students from grades 7–9, we assessed aggression motives via self‐report, along with self‐report of bullying perpetration and victimization, which were used to assign students into categories of Pure Bully, Bully/Victim (B/V), Pure Victim, and Uninvolved. Two structural models were computed to examine the relationship between these four categories of bullying involvement and aggression motives, using conservative and liberal bullying cutoffs. As predicted, B/V status was more strongly related to Rage and Revenge motives. However, B/Vs had higher scores than Pure Bullies for almost all aggression motives, including Recreation. We discuss the implications of addressing Revenge and Recreation, as well as Reward and Rage (which map most clearly to proactive and reactive aggression, respectively) aggression motives, for bullying prevention and intervention strategies, especially among adolescents for whom extant bullying prevention strategies may be ineffective or counterproductive.